Serum Level of Lactate Dehydrogenase is a Useful Clinical Marker to Monitor Progressive Multiple Myeloma Diseases: A Case Report - Hava Üsküdar Teke; Mustafa Başak; Deniz Teke; Mehmet Kanbay (Turkish Journal of Hematology, 2014)
To follow the progression of multiple myeloma (MM) disease, serum lactate dehydrogenase (LDH) levels are as useful markers as beta-2 microglobulin and monoclonal immunoglobulin. With this study, we have presented a case of a patient with a multiple myeloma which was fulminant course, whose LDH levels were normal at the onset of diagnosis increasing as 27 times more than normal as the disease progressed and who showed the development of extramedullary plasmacytomas. The patient, an 80-yearold female, was diagnosed with stage IIIA IgA type multiple myeloma and melphalan-prednisolon (MP) treatment was started. Although the LDH levels were low during the diagnosis and chemotherapy, the LDH levels increased up to 7557 U/L following the progression and occurrence of extramedullary plasmacytomas and the patient died. During the observation of the patient with MM, if the LDH levels are abnormally high, the progression of the disease should be considered after eliminating the other causes. Bone marrow aspiration and biopsy should be examined and the progression or relapse should be shown. On the other hand, the patients with LDH levels are high should be considered to have added plasmacytomas, the whole body should be examined at an early stage before the development of clinical symptoms and early treatment should be started.